Estimation of Salivary Lactate Dehydrogenase (LDH) in Healthy Adults - Imam, Fakhrul; Rabbani, Fazlay; Sultana, Amrin; Sultana, Jachmen; Talukder, Md Ali Hossain; Hasnat, Abul; Hasan, Md Zakirul; Ferdous, Ruhi (Journal of Dentistry and Allied Science, 2025)
Background: Saliva is recognized as a promising diagnostic fluid due to its non-invasive nature and ability to reflect systemic and oral health. Among salivary biomarkers, lactate dehydrogenase (LDH) holds diagnostic value as a cytoplasmic enzyme released during cellular injury or necrosis. Establishing normative salivary LDH levels is critical for distinguishing physiological from pathological states. Objective: To estimate the concentration of salivary LDH in healthy adults to establish reference values. Methods: This cross-sectional observational study was conducted over six months (May to November 2017) at the Dept. of Oral and Maxillofacial Surgery, Dhaka Dental College. Thirty healthy adults (30–65 years) were enrolled via convenience sampling. Unstimulated whole saliva was collected in the morning and LDH levels were assessed using validated enzymatic biochemical assay. Data were analyzed using SPSS v22.0, and Student’s t-test assessed gender differences. Results: The mean salivary LDH level was 408.7 U/L (SD: 401.6 U/L). No significant difference was observed between male and female participants (p > 0.05). Conclusion: This study provides preliminary reference values for salivary LDH in healthy adults, which may support future diagnostic applications. Further research on larger, demographically diverse populations is warranted. Journal of Dentistry and Allied Science, Vol. 8 No 2: 48-53